2015
DOI: 10.1097/igc.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyclooxygenase-2 Expression in Uterine Carcinosarcoma on Survival

Abstract: In view of the role of COX-2 in carcinogenesis, our finding that COX-2 expression may confer a better survival in patients with carcinosarcoma is intriguing. Larger studies are indicated to elucidate the effect of COX-2 expression on survival in patients with carcinosarcoma because this may have therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Brasky et al demonstrated that treatment of aspirin could reduce the risk of EC, especially in estrogen-mediated cases by analyzing 22,268 female Americans after up to 10 years [37]. In clinical studies, the correlation of COX-2 expression and EC patients' prognosis still remains conflicting [38,39]. PGE 2 is associated with both endometrial functions and disorders.…”
Section: Cox-2 and Endometrial Cancermentioning
confidence: 99%
“…Brasky et al demonstrated that treatment of aspirin could reduce the risk of EC, especially in estrogen-mediated cases by analyzing 22,268 female Americans after up to 10 years [37]. In clinical studies, the correlation of COX-2 expression and EC patients' prognosis still remains conflicting [38,39]. PGE 2 is associated with both endometrial functions and disorders.…”
Section: Cox-2 and Endometrial Cancermentioning
confidence: 99%
“…In osteosarcoma, a recent meta-analysis found that COX-2 expression predicted reduced 2-year overall and disease-free survival, without significant association with age, gender, tumor location, histology, stage, metastasis, or necrosis [27]. COX-2 has been shown to be upregulated in uterine carcinosarcoma [28].…”
Section: Introductionmentioning
confidence: 99%